ENT 530 : Inhanna / Nurul Sahida Abdul Majid - Abdul Majid, Nurul Sahida (2018)
This report was commissioned to apply fundamental entrepreneurial knowledge in creating and managing a business. This assignment allows me to apply new ideas using available resources and ICT tools in a dynamic entrepreneurship environment. In addition, throughout this semester I be able to analyse, resolve business and entrepreneurial decisions, able to demonstrate positive entrepreneurial values that involve opportunity seeking, proactivity and creativity.